BUMDES BUSINESS PLANNING WITH CANVAS BUSINESS MODEL IN THE VILLAGE AGREED KUTAI KARTANEGARA: PERENCANAAN BISNIS BUMDes DENGAN KANVAS MODEL BISNIS DI DESA SEPAKAT KUTAI KARTANEGARA - Doddy Adhimursandi; Rio Haribowo; Ariesta Heksarini; Musdalifah Azis (Yayasan Education and Social Center, 2022)
Village-Owned Enterprises (BUMdes) are business entities who’s entire or most of the capital is owned through direct participation originating from separated village assets to manage service assets and other businesses for the most excellent welfare of the village community. However, usually, BUMdes administrators tend to experience uncertainty when starting their business. Therefore, we need a work plan made by BUMdes in the field of entrepreneurship. These activities must be written and official to run their business because BUMdes is like a company, so planning and mapping are needed and later will require an evaluation process of the business model they have established. One way to simplify business model mapping and analysis is to use the Business Model Canvas by drawing nine canvas blocks. The nine blocks are interrelated with each other so that companies can design and evaluate strategies in each of the canvas blocks. This service is carried out in the village of Sepakat Loa Kulu, Kutai Kartanegara. This community service activity uses the training method and structured assistance. The result of this activity is that the BUMDes members in the village agree that Loa Kulu Kutai Kartanegara can plan the BUMDes business by using the Business Model Canvas to facilitate the mapping and analysis of the BUMDes business model in the Sepakat Village with the ultimate goal of advancing the economy in the Sepakat Village of Kutai Kartanegara